Neotenic formation in laboratory colonies of the termite Coptotermes gestroi after orphaning - Costa-Leonardo, A. M.; Arab, A.; Casarin, F. E. (Univ Arizona, 2004)
The termite Coptotermes gestroi (Wasmann 1896) ( Rhinotermitidae: Coptotermitinae) is an exotic species in Brazil and information concerning its reproductive developmental biology is scarce. We induced the formation of neotenics in laboratory colonies through orphaning experiments. Orphaning experiments were conducted in three-year old colonies of C. gestroi kept under laboratory conditions. After three months, eight nymphoid neotenics were observed in one colony after queen removal. Histological analysis showed that these neotenics were non-functional. The results suggest that these individuals may have arisen from the first nymphal instar (N1) or from an early N1 instar after one or two larval moults. Neotenics also were recorded on two incipient colonies of C. gestroi that lost the queen naturally.
Keywords: subterranean termites; castes; nymphoid reproductives; queen replacement; orphaning